Sex differences in metabolic regulation and diabetes susceptibility - Tramunt, Blandine; Smati, Sarra; Grandgeorge, Naia; Lenfant, Françoise; Arnal, Jean-François; Montagner, Alexandra; Gourdy, Pierre (Diabetologia, 2020)
Gender and biological sex impact the pathogenesis of numerous diseases, including metabolic disorders such as diabetes. In most parts of the world, diabetes is more prevalent in men than in women, especially in middle-aged populations. In line with this, considering almost all animal models, males are more likely to develop obesity, insulin resistance and hyperglycaemia than females in response to nutritional challenges. As summarised in this review, it is now obvious that many aspects of energy balance and glucose metabolism are regulated differently in males and females and influence their predisposition to type 2 diabetes. During their reproductive life, women exhibit specificities in energy partitioning as compared with men, with carbohydrate and lipid utilisation as fuel sources that favour energy storage in subcutaneous adipose tissues and preserve them from visceral and ectopic fat accumulation. Insulin sensitivity is higher in women, who are also characterised by higher capacities for insulin secretion and incretin responses than men; although, these sex advantages all disappear when glucose tolerance deteriorates towards diabetes. Clinical and experimental observations evidence the protective actions of endogenous oestrogens, mainly through oestrogen receptor α activation in various tissues, including the brain, the liver, skeletal muscle, adipose tissue and pancreatic beta cells. However, beside sex steroids, underlying mechanisms need to be further investigated, especially the role of sex chromosomes, fetal/neonatal programming and epigenetic modifications. On the path to precision medicine, further deciphering sex-specific traits in energy balance and glucose homeostasis is indeed a priority topic to optimise individual approaches in type 2 diabetes prevention and treatment.